Orientation transitions during the growth of imine covalent organic framework thin films. Issue 21 (17th May 2017) - Wang, H.; He, B.; Liu, F.; Stevens, C.; Brady, M. A.; Cai, S.; Wang, C.; Russell, T. P.; Tan, T.-W.; Liu, Y.
Abstract : The first experimental observation of a rare re-entrant transition during COF thin film growth reveals independent nucleation and growth kinetic processes. Abstract : Oriented growth of thin films of covalent organic frameworks (COFs) has attracted significant interest as the anisotropically aligned channels provide ideal nanoscopic domains that can facilitate mass transport or charge percolation. Despite some experimental progress in achieving oriented COF thin films, little is known about the kinetics and thermodynamics associated with the orientation or control over the solution-based growth process. We performed a systematic study of the thin film growth of an imine-based COF as a function of concentration and growth time. Grazing incidence wide-angle X-ray scattering (GIWAXS) was used to reveal the orientation and evolution of crystallization within the thin films at sequential growth stages. An unusual re-entrant transition from an oriented to disoriented to reoriented state was discovered, which correlates with the kinetics associated with independent surface- and solution-based nucleation and growth processes, as well as reorganization of disoriented COF crystallites.